Macrophage regulation of the “second brain”: CD163 intestinal macrophages interact with inhibitory interneurons to regulate colonic motility - evidence from the Cx3cr1-Dtr rat model - Yip, Jackson L. K.; Xavier, Soniya; Balasuriya, Gayathri K.; Hill-Yardin, Elisa L.; Spencer, Sarah J. (Frontiers in Immunology, 2023)
Intestinal macrophages are well-studied for their conventional roles in the immune response against pathogens and protecting the gut from chronic inflammation. However, these macrophages may also have additional functional roles in gastrointestinal motility under typical conditions. This is likely to occur via both direct and indirect influences on gastrointestinal motility through interaction with myenteric neurons that contribute to the gut-brain axis, but this mechanism is yet to be properly characterised. The CX3CR1 chemokine receptor is expressed in the majority of intestinal macrophages, so we used a conditional knockout Cx3cr1-Dtr (diphtheria toxin receptor) rat model to transiently ablate these cells. We then utilized ex vivo video imaging to evaluate colonic motility. Our previous studies in brain suggested that Cx3cr1-expressing cells repopulate by 7 days after depletion in this model, so we performed our experiments at both the 48 hr (macrophage depletion) and 7-day (macrophage repopulation) time points. We also investigated whether inhibitory neuronal input driven by nitric oxide from the enteric nervous system is required for the regulation of colonic motility by intestinal macrophages. Our results demonstrated that CD163-positive resident intestinal macrophages are important in regulating colonic motility in the absence of this major inhibitory neuronal input. In addition, we show that intestinal macrophages are indispensable in maintaining a healthy intestinal structure. Our study provides a novel understanding of the interplay between the enteric nervous system and intestinal macrophages in colonic motility. We highlight intestinal macrophages as a potential therapeutic target for gastrointestinal motility disorders when inhibitory neuronal input is suppressed.